Analisa Penggunaan Aplikasi Android Meter Reading PDAM Terhadap Kepuasan Pelanggan - Hardiyan Hardiyan (LPPM Universitas Bina Sarana Informatika, 2018)
Abstract―Application Meter Reading is an android-based application that PDAM uses to accelerate and minimize errors that customers often complain about. This study aims to analyze the effect of using android-based meter reading applications on customer satisfaction in PDAM TKR Tigaraksa Branch. The method used is descriptive verifikatif, with the intent to find the influence between independent variables with dependent variable. The sampling technique used in the study was analyzed by regression and correlation. Based on the research results obtained correlation coefficient = 0.100 which means that this value is very low and unidirectional category. If the application of meter reading is good then customer satisfaction will increase. Based on hypothesis test results where tcount (= 0.996) <ttabel (= 1,661) it can be interpreted that the application of meter reading does not affect customer satisfaction in PDAM TKR Tigaraksa Branch.